Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41417-020-00278-1
|View full text |Cite
|
Sign up to set email alerts
|

TAF1A and ZBTB41 serve as novel key genes in cervical cancer identified by integrated approaches

Abstract: Cervical cancer (CC) is the second most common cancer and the leading cause of cancer mortality in women. Numerous studies have found that the development of CC was associated with multiple genes. However, the mechanisms on gene level are enigmatic, hindering the understanding of its functional roles. This study sought to identify prognostic biomarkers of CC, and explore their biological functions. Here we conducted an integrated analysis to screen potential vital genes. Candidate genes were further tested by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Thus, dual targeting of MLLT11 and TRIL might help prevent the progression of EC. Coupled with our previous findings on protein complex, 18 we demonstrate that binding of MLLT11-TRIL has catalytic effect on phosphorylation of AKT-threonine 308, and might be a therapeutic target in EC.…”
Section: Introductionsupporting
confidence: 86%
“…Thus, dual targeting of MLLT11 and TRIL might help prevent the progression of EC. Coupled with our previous findings on protein complex, 18 we demonstrate that binding of MLLT11-TRIL has catalytic effect on phosphorylation of AKT-threonine 308, and might be a therapeutic target in EC.…”
Section: Introductionsupporting
confidence: 86%
“…The WGCNA package in R software was used to study the correlation patterns between genes as previously described, 14 and the gene modules related to clinical information were obtained. Pearson correlation coefficient between genes were calculated, and a weighted adjacency matrix a mn = |C mn | β was constructed, where a mn represents the adjacency coefficient between gene m and gene n; C mn represents the Pearson correlation coefficient between gene m and gene n. The scale‐free network was ensured by selecting the soft threshold β = 7, and the minimum module size was set to 30 genes.…”
Section: Methodsmentioning
confidence: 99%
“…The WGCNA package in R software was used to study the correlation patterns between genes as previously described, 14 and the gene modules related to clinical information were obtained.…”
Section: Establishment Of Weighted Co-expression Network Analysismentioning
confidence: 99%
“…In addition, the pathological process of various diseases, such as cancer, nervous system, and skeletal muscle system diseases are also related to BTB protein (Chaharbakhshi & Jemc, 2016; Jin et al, 2017; Leeman‐Neill & Bhagat, 2018; Y. Liu et al, 2018). In a previous study, we have found that ZBTB41, which is homologous to ZBTB34, was a crucial biomarker affecting the progression of cervical cancer (M. Wang, Liao, et al, 2020). In this study, through comprehensive multidatabase mining, we found that ZBTB34 is a hub gene for CRC progression.…”
Section: Discussionmentioning
confidence: 98%